If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 35x = 28x + 12 Reorder the terms: 4 + 35x = 12 + 28x Solving 4 + 35x = 12 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 4 + 35x + -28x = 12 + 28x + -28x Combine like terms: 35x + -28x = 7x 4 + 7x = 12 + 28x + -28x Combine like terms: 28x + -28x = 0 4 + 7x = 12 + 0 4 + 7x = 12 Add '-4' to each side of the equation. 4 + -4 + 7x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 7x = 12 + -4 7x = 12 + -4 Combine like terms: 12 + -4 = 8 7x = 8 Divide each side by '7'. x = 1.142857143 Simplifying x = 1.142857143
| z^2+0.04z+0.25=0 | | 1.89*12= | | 4d+7=-26d+5(6d-2) | | 9-w=4 | | -12/p=-3 | | 2l+3=7 | | 2(t-6)=6 | | 6-x+8=7x-1 | | u+97=7(5-u)+8u+62 | | 4(b-15)-4=8 | | ×/5-×/4=1 | | 8x-2=12x-3 | | X/5-×/4=1 | | 2=2(u-6)-2 | | In+Inx^2=6 | | 4/k=2 | | p+77=13(4-p)+14p-5 | | 4/k=12 | | 6/u=2 | | 9/b=3 | | 9x-1=6x+3 | | 3(j+1)=9 | | d+87=11(1-d)+12d+76 | | 12-7x-4-x=11-8x+2x | | 10x^2+5x+1=10 | | 10x^2+5x+5=0 | | 6/g=3 | | 10x^2+5x+1=0 | | z=0.5y*x^2 | | 2x^34=50 | | -1+9=3b-7-2b | | 6x+2x+5=2x |